ANALYSIS OF HUMANIZED CHILDBIRTH IN THE UNIFIED HEALTH SYSTEM (CIPEEX, 2025)
The demand for humanized childbirth in the public health system in Brazil has significantly increased in recent years due to the less invasive and safer nature of this procedure. Humanized childbirth aims to provide a welcoming and respectful environment for the pregnant woman, prioritizing her choices and promoting practices that reduce unnecessary interventions. In this context, health professionals are increasingly specializing to offer quality care that respects the needs and desires of women during childbirth. This study aims to understand how the choice for humanized childbirth occurs in the public health system, as well as to analyze the perceptions and challenges faced in this process. The methodology adopted for this research was content analysis of a report published by the newspaper Poder 360 in 2023, entitled "Humanized Childbirth Gains More and More Space in Hospitals." The report includes an interview with obstetrician Dr. Rômulo Negrini, a specialist in humanized childbirth, who provides insights into the evolution and growing demand for this type of childbirth in Brazil. The choice of this methodological tool is justified by the relevance of the source and the credibility of the interviewee, who offers a practical and updated view on the topic. In the data analysis, Negrini (2023) highlights that humanized childbirth, both in the public health system (SUS) and in the private sector, is gaining increasing acceptance among pregnant women and professionals in the field. Humanized childbirth is characterized by care that respects the woman's autonomy, provides physical and emotional support, and seeks to minimize unnecessary medical interventions whenever possible. Furthermore, Negrini emphasizes that humanized childbirth is not just a passing trend but a paradigm shift in childbirth care, being encouraged by public health policies and the women's movement itself in search of safer and more satisfying childbirth experiences. The choice for humanized childbirth within the SUS reflects the growing awareness among pregnant women about their rights and the importance of patient-centered health care. It is concluded that humanized childbirth is an excellent option for pregnant women, providing a positive and safe experience, both physically and emotionally. The growing demand for this type of childbirth in the Brazilian public health system indicates a significant transformation in how childbirth care is perceived and valued. However, for this type of care to be widely consolidated, continuous investments in professional training, adequate hospital infrastructure, and public policies that guarantee women's right to safe and respectful childbirth are necessary.
Keywords: Humanized childbirth; Comfort; Unified Health System